Wireless sensor network for internet of things facility management (IoT-FM) environment sensing - Tan, Yan Feng (Nanyang Technological University, 2022)
Environmental Quality (EQ) has always played an important role in the health of humans, with detrimental effects arising from elevated levels of pollutants. Regular monitoring of environmental parameters will help to mitigate and reduce such harmful effects on the health and wellbeing of humans. With recent advancements in wireless communications and Internet of Things (IoT) approach, it is possible to create and develop an IoT system for the purpose of monitoring EQ. IoT microcontrollers can be integrated with multiple environmental sensors that can be deployed at multiple indoor locations to form a low-cost, power efficient sensor module.